Tathwiir Kitaab al-Qawaaid al-'Arabiyyat Li Thullaab Qism Ta'liim al-Lughat al-'Arabiyyat Bi Jaami'at Mawlaanaa Maalik Ibraahiim al-Islamiyyat al-Hukuumyyat Maalaanj - Mukarromah, Muhimmatul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
This study aims to determine the development of textbooks for nahwu 2 and it effectiveness in the class. This study uses R&D research methods with the Dick and Carey model. The results of this study indicate that the use of the 'Qowaid book Nahwu 2 Material' in Nahwu 2 learning in class E, 3rd semester of the Department of Arabic Language Education, Faculty of Tarbiyah and Teacher Training, UIN Maulana Malik Ibrahim, Malang runs effectively. This is due to the evidence that the statistical results of (t) between the two classes (3,567) are more than the ttable level at the 5% level (1,740) and from the ttable level at the 1% level (2,567). The researcher concludes that the previous hypothesis is acceptable, and this shows that the use of the book 'Qowaid Nahwu 2 Material' in teaching Nahwu 2 is so effective